New construction method of periodic quasi-complementary sequence set - Xiaoyu CHEN; Chengrui WANG; Fan LIU (Tongxin xuebao)
To solve the problem that the number of sequences in the complete complementary sequence set is limited, periodic quasi-complementary sequence set was constructed.Firstly, based on the circular Florentine array, the near optimal periodic quasi-complementary sequence set was constructed by using the mapping function on <!--math xmlns="http://www.w3.org/1998/Math/MathML"> ℤ N </math--> .The obtained periodic quasi-complementary sequence sets had new subsequence lengths.Secondly, based on the one-coincidence frequency-hopping sequence set, the asymptotically optimal periodic quasi-complementary sequence set was constructed by defining the mapping function from <!--math xmlns="http://www.w3.org/1998/Math/MathML"> ℤ q </math--> to <!--math xmlns="http://www.w3.org/1998/Math/MathML"> ℤ q(q−1) </math-->.The comparison results show that compared with the existing periodic quasi-complementary sequence sets, the proposed method contains more sequences with the same subsequence length, and can support more users in multi-carrier communication system.